Atividade enzimática e índices de qualidade do solo: classes de interpretação em argissolo e latossolo subtropicais - Sobucki, Lisiane (2024)
Recent advances have been made in interpreting microbiological characteristics to help guide those working in the farms. However, the differences in soil, climate and agricultural practices in each location make it impossible to use universal reference values, so it is necessary to carry out regionalized studies. The interpretation of these properties is carried out by means of interpretation tables that can be associated with a soil quality index in order to obtain a diagnosis of the limits and potentials of each site. The main objective of this thesis was to propose interpretation classes for soil β-glucosidase and arylsulfatase enzymes and to use a soil quality index to evaluate different management practices adopted in Ultisols and Oxisols in Southern Brazil. The thesis was divided into three articles. In the first article, a review was made of the main contributions of soil enzymes to agriculture, with emphasis on the dynamics of soil elements and the environmental factors that modulate their activity. The review showed that there are many gaps in knowledge on this topic and that enzyme activity interpretation tables need to be calibrated for different soils and crops. In the second article, interpretation classes for enzymes in an Ultisol were proposed and a soil quality index (IQSFERTBIO) was tested to evaluate the quality of different soil preparation and cropping systems. The interpretation classes "Low", "Moderate" and "Adequate" were (in p-nitrophenol g-1 soil h-1) ≤ 19, 20-52 and > 52 for β-glucosidase and ≤ 53, 54 -147 and >147 for arylsulfatase. IQSFERTBIO was efficient in diagnosing soil quality and indicated the need to implement systems with limited soil disturbance. In the third article, interpretation classes for soil enzymes were proposed through the definition of critical limits, soil quality was demonstrated through chemical and microbiological properties of the soil, and soil management resulted in a balance between enzymatic activity and soil organic carbon in Oxisol. The interpretation classes "Low", "Moderate" and "Adequate" were (in p-nitrophenol g-1 soil h-1) for β-glucosidase of ≤ 54, 54-98 and > 98 and for arylsulfatase of ≤ 58, 59-130 and > 130, respectively. IQSFERTBIO, together with a quadrant analysis, explained that the direct planting system, combined with crop rotations with high plant diversity, should be prioritized to maintain high soil quality. The interpretation classes defined for Argisol and Oxisol were different, which reinforces regional studies taking into account the soil type. On the other hand, systems with low soil disturbance and high crop diversity should be prioritized to ensure soil quality regardless of soil type.